Universities Research Performance in the United Arab Emirates and Oman: Challenges of Higher Education Systems - Mohammed Aboelenein; Daria Salnikova; Tatiana Karabchuk; Aizhan Shomotova (Ali Khorsandi Taskoh, 2022)
This article analyzes research performance in universities in two member countries of the Gulf Cooperation Council (GCC): the United Arab Emirates (UAE) and the Sultanate of Oman. Both have introduced reforms, innovations, and investments into their educational systems. Many international university branches were established, but their impact on research performance has yet to be closely evaluated. The article includes the following: first, descriptive analysis of research performance through total number of publications, citable documents, and average number of citations per document; second, analysis of priority subject areas and an overview of university rankings; third, challenges for research in higher educational institutions. Among sociocultural predictors of academic performance are historical context, English language proficiency, the modern educational system's drawbacks, and higher education's privatization and commercialization. Highlighted are institutional and organizational obstacles related to employment conditions of expatriates, along with the research environment and challenges that hinder internationalization.